2020
DOI: 10.22271/chemi.2020.v8.i6ah.11130
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of groundnut (Arachis hypogaea L.) genotypes under varying plant densities and seasons

Abstract: The experiment was conducted at the Education and Research Farm of the Department of Botany, College of Agriculture, Dapoli, Dist. Ratnagiri, Maharashtra state during the period from Kharif and Rabbi 2017-18 and 2018-19 to study the yield performance of groundnut genotypes under varying plant densities and seasons. The experiment was laid out in a split plot design with three replications. Results showed that different treatments had significant influence on growth and yield contributing characters. Crop sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…According to the observations taken during the systematic conduction of the experiment with good maintenance of the experimental plots, we have concluded that as the branching of groundnut increases, the yield also increases, respectively. However, the extent of increase in yield and branching varies for different treatments and those differences in the yield obtained were given below: The number of branches led to an increase in yield based on different types of treatments in different experiments were reported in findings of Shashidhar VR, et al [3], Gowthami V, et al [4], Nigam SN, et al [5], Ali FM, et al [6], Avinasha BL, et al [7], Nagar R, et al [8], Oppong SD, et al [9], Thilini SPLNK, et al [10], Gawas D, et al [11], Magagula N, et al [12], Sathiya K, et al [13], Mohanty P, et al [14], Ibrahim II, et al [15], Yilmaz M, et al [16], Iddrisu A, et al [17], Singh N, et al [18], El Naim AM, et al [19], Seijo G, et al [20], Maleki SJ, et al [21], Michael CY, et al [22], Sanders TH, et al [23,24], Veeramani P, et al [25].…”
Section: Resultsmentioning
confidence: 98%
“…According to the observations taken during the systematic conduction of the experiment with good maintenance of the experimental plots, we have concluded that as the branching of groundnut increases, the yield also increases, respectively. However, the extent of increase in yield and branching varies for different treatments and those differences in the yield obtained were given below: The number of branches led to an increase in yield based on different types of treatments in different experiments were reported in findings of Shashidhar VR, et al [3], Gowthami V, et al [4], Nigam SN, et al [5], Ali FM, et al [6], Avinasha BL, et al [7], Nagar R, et al [8], Oppong SD, et al [9], Thilini SPLNK, et al [10], Gawas D, et al [11], Magagula N, et al [12], Sathiya K, et al [13], Mohanty P, et al [14], Ibrahim II, et al [15], Yilmaz M, et al [16], Iddrisu A, et al [17], Singh N, et al [18], El Naim AM, et al [19], Seijo G, et al [20], Maleki SJ, et al [21], Michael CY, et al [22], Sanders TH, et al [23,24], Veeramani P, et al [25].…”
Section: Resultsmentioning
confidence: 98%
“…Groundnut kernels contain 40-50% oil, widely used in cooking and is rich in vitamins A, B and E. It is also valued as a rotation crop and as a legume, it aids in nitrogen fixation and improves soil health. Globally, groundnut is cultivated in over 100 countries on 29.5 million hectares, producing 48.7 million metric tonnes with an average yield of 1.6 metric tonnes ha -1 [1]. Developing countries contribute significantly, accounting for 97% of the cultivation area and 94% of the production.…”
Section: Introductionmentioning
confidence: 99%